Towards an integrated science of aesthetics: Getting rid of the main misunderstandings in evolutionary aesthetics - PORTERA, Mariagrazia (Fragmentum, 2019)
Evolutionary Aesthetics is a bourgeoning and thriving sub-field of Aesthetics, the main aim of which is “the importation of aesthetics into natural sciences, and especially its integration into the heuristic of Darwin’s evolutionary theory.” Notwithstanding the growing popularity in the past two decades, a look into the state of current research in Evolutionary Aesthetics suggests a significant degree of haziness in the field from both epistemological-methodological and theoretical points of view. The main aim of the present paper is to evaluate consistency and coherence of the Evolutionary Aesthetics’ research programme against the background of Boix Mansilla’s epistemic criteria for interdisciplinary research programmes, and to assess the potential of epigenetics and niche construction theory as two new promising research avenues in a revised, updated Evolutionary Aesthetics.